Optimization of Pelvic MRI for Suspected Malignant Ovarian Cystoma Through Intraluminal Ultrasound Gel Administration and the Addition of an Axial T2-FFE Sequence at Gambiran Public Hospital - Diah Ranu Etikasari; Rita Dewi Sunarno (Master of Public Health Program Institut Ilmu Kesehatan STRADA Indonesia, 2026)
Suspected malignant cystoma ovarii poses diagnostic challenges in pelvic MRI due to collapsed inferior pelvic boundaries (vagina, rectum, uterus), hindering lesion infiltration assessment. Standard MRI protocols are suboptimal for detecting hemorrhage within lesions, necessitating technique modifications to enhance diagnostic accuracy in resource-limited settings like RSUD Gambiran, Kediri City. Objective: To describe the role of intraluminal ultrasonic gel administration (pervaginal and perrectal) and addition of axial T2-FFE sequence in optimizing pelvic MRI protocols for suspected malignant cystoma ovarii cases. Methods: Qualitative case study on one reproductive-age female patient diagnosed with cystoma ovarii. Key informants included performing radiographer, expert radiologist reader, and referring physician. Data collected via procedure observation, in-depth interviews, and image documentation. Narrative interactive analysis applied. Protocol: MRI safety screening, renal function tests (BUN/creatinine), 50 cc ultrasonic gel insertion pervaginally/perrectally, sequences T2W TSE/SPAIR, T1W TSE/SPIR, DWI, plus T2-FFE axial. Results: Ultrasonic gel distended vaginal/rectal lumens, clearly delineating anatomical boundaries with uterus (rectouterine pouch, rectovaginal septum), facilitating infiltration evaluation without plane obliteration. Axial T2-FFE revealed no hemorrhagic components in the lesion, aiding cyst content characterization. Conclusion: Protocol modifications using ultrasonic gel and T2-FFE axial enhance pelvic MRI image quality, supporting accurate diagnosis of suspected malignant cystoma ovarii through superior organ boundary visualization and blood product detection. Recommended for complex adnexal cases in limited facilities, despite transient patient discomfort.